2020
DOI: 10.1038/s43016-020-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Innovation can accelerate the transition towards a sustainable food system

Abstract: Future technologies and systemic innovation are critical for the profound transformation the food system needs. These innovations range from food production, land use and emissions, all the way to improved diets and waste management. Here, we identify these technologies, assess their readiness and propose eight action points that could accelerate the transition towards a more sustainable food system. We argue that the speed of innovation could be significantly increased with the appropriate incentives, regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
255
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(312 citation statements)
references
References 36 publications
2
255
0
2
Order By: Relevance
“…Examples of external relevant factors are climate change, water shortages, outbreaks of food-borne diseases, as well as the geographical distribution of these putative events, which may differently stress either a faster or a slower development for each plant-and cell-based meat alternatives. Furthermore, we highlight again that as potential consumers worldwide have socially engrained relationships to food (Herrero et al, 2020), expressed as established local habits and traditions, the acceptance of meat substitutes may not be straightforward. Considering all the complexities, however, it seems clear that a major disruptive change is on the horizon, which warrants forecasting efforts from a variety of perspectives.…”
Section: Scenario Forecastingmentioning
confidence: 96%
See 2 more Smart Citations
“…Examples of external relevant factors are climate change, water shortages, outbreaks of food-borne diseases, as well as the geographical distribution of these putative events, which may differently stress either a faster or a slower development for each plant-and cell-based meat alternatives. Furthermore, we highlight again that as potential consumers worldwide have socially engrained relationships to food (Herrero et al, 2020), expressed as established local habits and traditions, the acceptance of meat substitutes may not be straightforward. Considering all the complexities, however, it seems clear that a major disruptive change is on the horizon, which warrants forecasting efforts from a variety of perspectives.…”
Section: Scenario Forecastingmentioning
confidence: 96%
“…However, there are uncertainties as to the exact proportions of total meat market to be substituted, which are challenging for scenario forecasting. For instance, although recent research has shown that cell-and plant-based meat substitutes may be accepted or at least tried by consumers in a diversity of countries like Brazil, Germany, Italy, India, China, and the United States (Bryant et al, 2019;Mancini and Antonioli, 2019;Valente et al, 2019;Weinrich et al, 2019), some of those products do not exist so far (e.g., cell-based meat products), and more nuanced insights into the cultural and social barriers for introducing food innovation are still needed (Herrero et al, 2020), as they can challenge an exclusively technical understanding of dietary changes (Noack and Pouw, 2015). Thus, even though the need for a profound transformation of the food systems is recognized (Herrero et al, 2020), projections must be cautiously interpreted.…”
Section: Scenario Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is widely recognised that new technologies and systemic innovation are critical for the profound transformation the food system needs [1]. Cell-based meat is an alternative to conventional meat that does not require the husbandry and slaughtering of animals [2].…”
Section: Introductionmentioning
confidence: 99%
“…This should include: (i) providing guidelines and establishing pilots for efficient and sustainable conversion of livestock production to plant production in collaboration with the farmer advisory services, (ii) targeting subsidies towards production of plant-based food commodities [47], coupled with (iii) implementing measures for increasing the capability, opportunity, and motivation of consumers that will make it easier and more acceptable for them to make a primarily plant-based and healthy diet the preferred choice [71][72][73], and iv) considering adopting a carbon tax on food, as suggested by the Danish Council on Climate Change [20]. New actors in the market, such as producers of plant-based alternatives to meat and dairy, can potentially accelerate this transition because they are not invested in maintaining the status quo as more established actors are [74].…”
Section: Discussionmentioning
confidence: 99%